Cerebral Venous Thrombosis in the University Hospital of Ouagadougou in Burkina Faso - Lompo, Djingri Labodi; Nacanabo, Assami; Zoungrana, Alassane; Kere, D Fabienne; Gnampa, Melody Z; Kyelem, Adeline Julie Marie; Napon, Christian; Millogo, Athanase; Kabore, Raphael Marie Patrick (British Journal of Healthcare and Medical Research, 2025)
Introduction: Cerebral venous thrombosis (CVT) accounts for less than 1% of strokes in Western countries, and probably more in sub-Saharan Africa (SSA). The aim of this study was to investigate CVT in the University Hospital Centres (UHC) of Ouagadougou in Burkina Faso. Patients and methods: This was a prospective, multicentre, cross-sectional hospital-based study in the University Hospital of Ouagadougou, Burkina Faso, from 1 June 2018 to 31 January 2023. It concerned patients admitted for CVT confirmed by the demonstration of a thrombus seated in the dural sinus and/or cortical vein on brain CT or MRI. The socio-demographic, clinical, paraclinical, aetiological and evolutionary characteristics of the patients were analysed using Epi-Info 7.2.5.0 software. Results: We consecutively included 37 patients (1% of all strokes), predominantly female (64.9%), with an average age of 38.2 years. The clinical picture was polymorphous, dominated by focal neurological deficit in 24 cases (64.9%), intracranial hypertension (ICHT) in 18 cases (48.6%) and epileptic seizures in 12 cases (32.4%). On neuroimaging, the most frequent topographies were the lateral sinus with 23 cases (62%), followed by the superior sagittal sinus with 16 cases (43%) and multiple localisations with 9 cases (24%). Cerebral oedema in 18 cases (48.6%), cerebral infarction in 7 cases (18.9%) and meningoencephalitis in 6 cases (16.2%) were the other cranioencephalic lesions most frequently found on neuroimaging. Isolated or associated aetiological factors were found in 29 patients (78.4%), dominated by gynaeco-obstetrical factors in 13 patients (35.1%) and cervicocephalic infections in 12 patients (32.4%). Clinical outcome on curative anticoagulants was favourable in 35 patients (94.6%); 2 patients (5.4%) died in hospital. Conclusion: CVT accounts for 1% of strokes in Ouagadougou. Our study confirms the clinical and paraclinical polymorphism and good prognosis of CVT. However, aetiological factors are dominated by gravidopuerperal factors and cervicocephalic infections.